The Influence of Price and Quantity on Sales Mediated by Promotions (Study at PT The Univenus for the 2019-2023 Period) - Prabowo, Stanley; Sopiah, Sopiah; Zagladi, Arief Noviarakhman (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
This study aims to investigate the influence of price and quantity on sales mediated by promotions at PT The Univenus during the 2019–2023 period. This study uses a quantitative approach as the research method, this study examines the relationship between independent variables (price and quantity) and dependent variables (sales) with promotion as a mediating variable whose data is processed by the SEM-PLS method. The results show that price and quantity have a significant influence on sales, and promotions reinforce this relationship. Competitive pricing increases sales volume, especially when products are promoted, as well as adequate quantities encourage larger purchases in a multi-unit promotional strategy. Effective promotions not only increase short-term sales but also help build brand loyalty. This study fills a gap in the literature on the interaction of price elasticity, promotion, and consumer response in the manufacturing industry. To increase sales and market position. From the results of this study, PT The Univenus is recommended to implement effective promotional strategies, such as multi-unit discounts and competitive prices.